Reform cinema in Iran : film and political change in the Islamic Republic - Atwood, Blake Robert, 1983- (New York : Columbia University Press, 2016)
It is nearly impossible to separate contemporary Iranian cinema from the Islamic revolution that transformed film production in the country in the late 1970s. As the aims of the revolution shifted and hardened once Khomeini took power and as an eight-year war with Iraq dragged on, Iranian filmmakers confronted new restrictions. In the 1990s, however, the Reformist Movement, led by Mohammad Khatami and the film industry, developed an unlikely partnership that moved audiences away from revolutionary ideas and toward a discourse of reform. In Reform Cinema in Iran, Blake Atwood examines how new i.
Introduction: revolutionary cinema and the logic of reform -- When love entered cinema: mysticism and the emerging poetics of reform -- Screening reform: campaign movies, documentaries, and urban Tehran -- Video democracies: or, the death of the filmmaker -- Who killed the tough guy? continuity and rupture in the filmfarsi tradition -- Film archives and online videos: the search for reform in post-Khatami Iran -- Conclusion: Iran's cinema museum and political unrest.
Includes bibliographical references and index.
Includes filmography.
Online resource; title from PDF title page (JSTOR, viewed on December 31, 2018).
JSTOR
Keywords: Motion pictures -- Iran -- History -- 20th century; Motion pictures -- Iran -- History -- 21st century; Motion pictures -- Political aspects -- Iran; Motion picture industry -- Political aspects -- Iran -- 20th century; Cinéma -- Iran -- Histoire -- 20e siècle.; Cinéma -- Iran -- Histoire -- 21e siècle.; Cinéma -- Industrie -- Aspect politique -- Iran -- 20e siècle.; Cinéma -- Aspect politique -- Iran; HISTORY -- Middle East -- General; Motion picture industry -- Political aspects; Motion pictures; Motion pictures -- Political aspects; Iran; 1900-2099; History